Upaya Hukum Perlindungan Konsumen Dalam Menuntut Ganti Rugi Atas Kerugian Akibat Produk Cacat - Sonya Agus Suryani; Syukran Harbelin; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Consumer protection is a crucial aspect of the state's responsibility in ensuring justice and safety within economic activities. Consumers often face issues due to defective products, resulting in material and non-material losses. Law Number 8 of 1999 concerning Consumer Protection provides a strong legal foundation for claiming compensation for such losses. This study uses a normative juridical method with a literature-based approach, aiming to examine the legal remedies available to consumers and the role of consumer protection institutions in dispute resolution. The findings show that consumers can pursue compensation through both litigation and non-litigation channels, supported by institutions such as BPKN, LPKSM, and BPSK. These institutions play vital roles in consumer education, advocacy, mediation, and imposing administrative sanctions on business actors who violate regulations. Collaboration between consumers, the government, businesses, and related institutions is essential to building a fair, transparent, and safe market ecosystem for all members of society.